THE APPLICATION OF BALANCE IDEA IN SETTLEMENT OF DOCTOR MALPRACTICE CASE THROUGH PENAL MEDIATION - Yati Nurhayati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The current criminal acts of malpractice in the criminal justice system in Indonesia in its enforcement ignores the rights of victims of the crime in the criminal case handling process and the effect to be borne by the victims of the crime because of the legal protection for the victims of the crime does not receive adequate recognition. Based on this understanding the author made two formulations of the problem. First, how is the fulfillment of the rights of victims of doctor malpractice in the criminal justice system in Indonesia? Second, how is the implementation of balance idea in settling disputes of doctor malpractice through penal mediation? This research used normative juridical method. It can be concluded that first, the criminal justice system in Indonesia ignores the rights of victims of doctor malpractice and prioritize more on how to penalize the perpetrators of the malpractice. Second, the principle of balance idea in crime can be applied in resolving malpractice criminal cases through penal mediation where a doctor can be released from criminal penalties, subject to treat and recover the victims. Through the penal mediation the victims’ protection and fulfillment of their rights are preferred and the responsibilities to treat the victims are burdened the doctors. Keywords: Malpractice, penal mediation.